A Comparative Study of The Cost Risk of EPC Models for Engineering Construction at Home And Abroad. Issue 1 (September 2020) - Liu, Yang; Yang, Zuxian; Gan, Ying; Li, Yongbing; Huang, Yongqiang; Gao, Chengming; Yan, Ziwei; Liu, Ying; Gui, Yuhuan; Liu, Zhongjing
Abstract: EPC projects with large engineering and procurement volumes, long construction cycles and management difficulties, the risks faced are also more complex and varied than in other contracting models. This paper establishes a risk index system by documentary method and evaluates and calculates the cost risk in two different environments at home and abroad by hierarchical analysis, so as to find the similarities and differences and propose countermeasures to provide a basis for risk management in China's EPC contracting model.